2016
DOI: 10.3389/fmicb.2016.01940
|View full text |Cite
|
Sign up to set email alerts
|

Metabiotics: One Step ahead of Probiotics; an Insight into Mechanisms Involved in Anticancerous Effect in Colorectal Cancer

Abstract: Colorectal cancer is closely associated with environment, diet and lifestyle. Normally it is treated with surgery, radiotherapy or chemotherapy but increasing systemic toxicity, resistance and recurrence is prompting scientists to devise new potent and safer alternate prophylactic or therapeutic strategies. Among these, probiotics, prebiotics, synbiotics, and metabiotics are being considered as the promising candidates. Metabiotics or probiotic derived factors can optimize various physiological functions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 179 publications
(162 reference statements)
0
71
0
2
Order By: Relevance
“…In addition to that, studies have also reported that small interfering RNAs has been utilized for inhibition of HIV, influenza infection and hepatitis [88]. In continuation with this, certain amino acid derivatives including selenocysteines and selenomethionines, have been reported to be synthesized in yeasts and Lactobacilli [89]. They have been found to play protective role against cancer, counteract oxidative stress and activate anabolic pathways of thyroid hormone biosynthesis and modulate immune system.…”
Section: Miscellaneousmentioning
confidence: 90%
“…In addition to that, studies have also reported that small interfering RNAs has been utilized for inhibition of HIV, influenza infection and hepatitis [88]. In continuation with this, certain amino acid derivatives including selenocysteines and selenomethionines, have been reported to be synthesized in yeasts and Lactobacilli [89]. They have been found to play protective role against cancer, counteract oxidative stress and activate anabolic pathways of thyroid hormone biosynthesis and modulate immune system.…”
Section: Miscellaneousmentioning
confidence: 90%
“…Probiotics not only produce anti-inflammatory factors to extend the immune stimulating function, but also secrete antioxidant, anti-cancer compounds, short chain fatty acids to improve intestinal barrier function [51,52]. Cyclooxygenase-2 can promote tumor angiogenesis, while probiotics inhibit carcinogenesis by reducing cyclooxygenase-2's expression [53].…”
Section: Probiotics In the Inhibition Of Crcmentioning
confidence: 99%
“…This finding suggests that the addition of specific probiotic bacteria to lactic acid products can provide patients with both good postoperative nutrition and some therapeutic benefits. Microbes have also been shown to exert apoptosis via multiple mechanisms in HT29 and HCT116 cell lines; exerting cytotoxic effects on cancer cells, secreting specific cytotoxic metabolites, and positively regulating the C-fos gene [60]. Second, probiotics can enhance the function of the intestinal epithelial barrier.…”
Section: A New Weapon Against Cancer: the Emergence Of Micro-ecologicmentioning
confidence: 99%